Conflicting vascular and metabolic impact of the IL-33/sST2 axis. Issue 12 (2nd July 2018) - Altara, Raffaele; Ghali, Rana; Mallat, Ziad; Cataliotti, Alessandro; Booz, George W; Zouein, Fouad A
Abstract: Interleukin 33 (IL-33), which is expressed by several immune cell types, endothelial and epithelial cells, and fibroblasts, is a cytokine of the IL-1 family that acts both intra- and extracellularly to either enhance or resolve the inflammatory response. Intracellular IL-33 acts in the nucleus as a regulator of transcription. Once released from cells by mechanical stress, inflammatory cytokines, or necrosis, extracellular IL-33 is proteolytically processed to act in an autocrine/paracrine manner as an 'alarmin' on neighbouring or various immune cells expressing the ST2 receptor. Thus, IL-33 may serve an important role in tissue preservation and repair in response to injury; however, the actions of IL-33 are dampened by a soluble form of ST2 (sST2) that acts as a decoy receptor and is produced by endothelial and certain immune cells. Accumulating evidence supports the conclusion that sST2 is a biomarker of vascular health with diagnostic and/or prognostic value in various cardiovascular diseases, including coronary artery disease, myocardial infarction, atherosclerosis, giant-cell arteritis, acute aortic dissection, and ischaemic stroke, as well as obesity and diabetes. Although sST2 levels are positively associated with cardiovascular disease severity, the assumption that IL-33 is always beneficial is naïve. It is increasingly appreciated that the pathophysiological importance of IL-33 is highly dependent on cellular and temporal expression. Although IL-33 is atheroprotective and may prevent obesity and type 2 diabetes by regulating lipid metabolism, IL-33 appears to drive endothelial inflammation. Here, we review the current knowledge of the IL-33/ST2/sST2 signalling network and discuss its pathophysiological and translational implications in cardiovascular diseases.